Pengaruh Pengetahuan dan Sikap Terhadap Kesiapsiagaan Kepala Keluarga dalam Menghadapi Bencana Banjir - Santi Yatnikasari; Sigiet Haryo Pranoto; Fitriyati Agustina (Jurnal Teknik, 2020)
Floods are natural disasters that need attention because they threaten people's lives and economies. Samarinda is the capital city of East Kalimantan, one of the cities that is always plagued by flood problems. The purpose of this study was to determine how much influence the knowledge and attitudes about the risk of floods have on the preparedness of the head of the family in facing flood disasters. The population in this study was 735 households in the Sempaja Timur village, North Samarinda district, Samarinda city, and the sample was 199 households. This study uses a mixed-method that combines qualitative and quantitative approaches. The data instrument was taken using a questionnaire and analyzed with linear regression statistical analysis, and F-test statistical test. The results showed that there was a significant influence of knowledge and attitudes on the level of family head preparedness in facing floods in East Sempaja Village. This is proven in the multiple linear regression equation: Y = 10.282 + 0.243 X1 + 0.034 X2, and the results of the F-test with a significance level of α = 0.05 obtained a calculated F value of 8.031 and a P value of 0.000 <0.05, therefore knowledge and attitudes variable have simultaneous significant influences on the preparedness variable. The combined index of four parameters, namely knowledge and attitude, emergency response plans, resource mobilization and flood warning systems was 73.26. In the preparedness index classification, this number is in the ready category. This research is expected to give insight to the head of the family who is part of the community to increase awareness of the importance of knowledge and preparedness regarding flood disasters.